Using A High-Temperature Flue Gases in the Technology of Combustion Neutralization of Wastewater; MATEC Web of Conferences; Vol. 72 : Heat and Mass Transfer in the System of Thermal Modes of Energy – Technical and Technological Equipment (HMTTSC-2016) - Vysokomornaya O. V. Olga Valeryevna; Tsygankova Yu. S. Yuliya Sergeevna; Aykina N. N. Natalya; Ushmaev D. V. Denis (2016, 2016)
Title screen